A Q-smarandache pseudo clean ideals of BH-Algebra. (18th August 2022) - Jabbar, Ahmed Abdulhussein; Hussain, Ahmed Hadi
Abstract: In this paper, we studied some of the properties of a Q-Samarandache pseudo BH- algebra, a Q-Samarandache pseudo ideal, a pseudo clean ideal and a Q-Samarandache pseudo clean ideal of a Q-Samarandache pseudo BH-algebra respectively and so we presented the relationships between these types of ideals.